Auxetic Metamaterial Using Bistable Composite Laminates - Kumar A.; Haldar A. (My University, 2025)
This research focuses on the development of a novel auxetic metamaterial with bistable unit cells, aiming to achieve large shape transformations and potential applications in emergency shelters, bridges, space-based photovoltaic arrays, and among many others. Unlike traditional monostable auxetic materials, this design incorporates multi-sectioned fiber-reinforced composite laminates exhibiting bistability, combined with monostable symmetric laminates. The geometric nonlinear finite element analysis is conducted at two hierarchical levels to analyze the metamaterial's behavior. Upon the application of a concentrated load, the lattice exhibits auxetic behavior, with the extent of auxeticity increasing with the number of unit cells in a row. The design parameters such as the dimensions and fiber orientation of the bistable plate, as well as the number of composite laminate layers, influence the auxeticity and load-carrying capacity of the lattice. By tailoring these parameters, the metamaterial can be optimized for lightweight, load-bearing, auxetic, and bistable characteristics. This study contributes to the advancement of metamaterials with tunable properties for various engineering applications. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.